The Prospect Of Stainless Steel Foil Industry In Malaysia - Fen, Ong Swee (2002)
The case study is concerning a foreign investment company in Malaysia facing the threat of low operation cost in China. With the booming and developing China Market, the company seems to loss its competitive advantages of having operation in Malaysia. As such, the top management of the company is considering of the moving the operation to China. In the case study, the writer discussed the current performance of the company in Malaysia, key cost elements that affect the whole operation cost and concluded that it is more favorable for the company to maintain its operation in Malaysia.